THE IMPACT OF FINANCIAL LITERACY, SOCIAL CAPITAL, AND MANAGERIAL INNOVATION ON THE FINANCIAL PERFORMANCE OF MSMEs - Nursansiwi, Dwi Arini; Prathama, Baiq Desthania; Armiani, Armiani (Accounting Studies and Tax Journal (COUNT), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economy, especially in developing countries like Indonesia. However, many MSMEs face challenges in financial management that impact their financial performance. This research aims to explore the influence of financial literacy, social capital, and managerial innovation on the financial performance of MSMEs in Indonesia. The approach used is Systematic Literature Review (SLR) with bibliometric analysis, thematic analysis and content analysis of 29 relevant scientific articles. Data were collected from international databases such as Scopus and Web of Science, with a focus on publications between 2002 to 2024. Findings show that financial literacy and social capital significantly improve the financial performance of MSMEs, while managerial innovation serves as a mediator that strengthens the relationship. This research provides theoretical contributions by integrating the Resource-Based View, Social Capital Theory, and Dynamic Capabilities Theory, as well as practical implications for the development of more effective MSME empowerment programs. These findings are expected to help policy makers and practitioners in designing strategies that support the growth and sustainability of MSMEs.